Pre-purchase information search and consumer satisfaction: Replication and extension - D. Rousseau (South African Journal of Business Management, 1986)
In this paper the author examines consumer satisfaction with major household appliances and its determining factors. Hypotheses relating to pre-purchase information search and product satisfaction as well as previous satisfactory store experiences and subsequent repurchase behaviour are proposed and empirically tested using data from 55 consumers who patronized a large eastern Cape hypermarket. Results imply that product satisfaction is more related to market place variables than actual search behaviour. Repeat shopping intentions are associated with previous shopping experiences at the particular store which also contributes to product satisfaction. Marketing implications and future research directions are briefly discussed.
Keywords: 650